Synthesis and Hybrid SAR Property Modeling of Novel Cholinesterase Inhibitors - Kos, Jiri; Kozik, Violetta; Pindjakova, Dominika; Jankech, Timotej; Smolinski, Adam; Stepankova, Sarka; Hosek, Jan; Oravec, Michal; Jampilek, Josef; Bak, Andrzej (International journal of molecular sciences, 2021)
A library of novel 4-{[(benzyloxy)carbonyl]amino}-2-hydroxybenzoic acid amides was designed and synthesized in order to provide potential acetyl- and butyrylcholinesterase (AChE/BChE) inhibitors; the in vitro inhibitory profile and selectivity index were specified. Benzyl (3-hydroxy-4-{[2-(trifluoromethoxy)phenyl]carbamoyl}phenyl)carbamate was the best AChE inhibitor with the inhibitory concentration of IC50 = 36.05 µM in the series, while benzyl {3-hydroxy-4-[(2-methoxyphenyl)carbamoyl]phenyl}-carbamate was the most potent BChE inhibitor (IC50 = 22.23 µM) with the highest selectivity for BChE (SI = 2.26). The cytotoxic effect was evaluated in vitro for promising AChE/BChE inhibitors. The newly synthesized adducts were subjected to the quantitative shape comparison with the generation of an averaged pharmacophore pattern. Noticeably, three pairs of fairly similar fluorine/bromine-containing compounds can potentially form the activity cliff that is manifested formally by high structure-activity landscape index (SALI) numerical values. The molecular docking study was conducted for the most potent AChE/BChE inhibitors, indicating that the hydrophobic interactions were overwhelmingly generated with Gln119, Asp70, Pro285, Thr120, and Trp82 aminoacid residues, while the hydrogen bond (HB)-donor ones were dominated with Thr120. π-stacking interactions were specified with the Trp82 aminoacid residue of chain A as well. Finally, the stability of chosen liganded enzymatic systems was assessed using the molecular dynamic simulations. An attempt was made to explain the noted differences of the selectivity index for the most potent molecules, especially those bearing unsubstituted and fluorinated methoxy group.
Keywords: Cholinesterase Inhibitors; viabilita buněk; Cluster Analysis; simulace molekulární dynamiky; THP-1 Cells; ligandy; Cell Line, Tumor; Solvents; Structure-Activity Relationship; cholinesterase inhibition; THP-1 buňky; rozpouštědla; racionální návrh léčiv; Ligands; Molecular Dynamics Simulation; shluková analýza; Cell Survival; Molecular Docking Simulation; Inhibitory Concentration 50; analýza hlavních komponent; molecular docking; acetylcholinesterasa; molekulární modely; vztahy mezi strukturou a aktivitou; Aminosalicylic Acid; Principal Component Analysis; lipophilicity; similarity-activity landscape index; simulace molekulového dockingu; Models, Molecular; Carbamates; lidé; karbamáty; kyselina aminosalicylová; Humans; Butyrylcholinesterase; CoMSA; Drug Design; 4-aminosalicylanilides; carbamate synthesis; inhibiční koncentrace 50; nádorové buněčné linie; butyrylcholinesterasa; Acetylcholinesterase; cholinesterasové inhibitory